AN ANALYSIS OF THE ENGLISH LANGUAGE CURRICULUM FOR SENIOR HIGH SCHOOL ON 2013 CURRICULUM REVISION EDITION - Mulyani, Mulyani (Getsempena English Education Journal, 2018)
AbstractEnglish language curriculum is considered essential to be conducted appropriately and effectively. The appraisal of the curriculum which sits in the 2013 curriculum is highly needed to be conducted in order to find the appropriate and effective learning and teaching instruction in the classroom. The method applied in this study is a qualitative method in which the library research and the documentation of 2013 curriculum edition revision document were used. From the findings of study, it indicated that the English language curriculum which sits in the 2013 curriculum and its revision edition can be considered appropriate and effective for conducting language learning instruction in the classroom. It also meets the main goals stated in the curriculum as well as it meets the studentsâ needs and interests. Nevertheless, the results of this appraisal are still limited and have a few shortages since the curriculum is still new and is being applied in all schools in Indonesia.Â Keywords: Analysis, English Language Curriculum, 2013 Curriculum Edition Revision,Â Â Â Â Â Â  Senior High School